An MRPS12 mutation modifies aminoglycoside sensitivity caused by 12S rRNA mutations - Sonia eEmperador; Sonia eEmperador; Sonia eEmperador; David ePacheu-Grau; M. Pilar eBayona-Bafaluy; Nuria eGarrido-Pérez; Antonio eMartín-Navarro; Manuel José López-Pérez; Manuel José López-Pérez; Manuel José López-Pérez; Julio eMontoya; Julio eMontoya; et al. (Frontiers in Genetics, 2015)
Several homoplasmic pathologic mutations in mitochondrial DNA, such as those causing Leber hereditary optic neuropathy or non-syndromic hearing loss, show incomplete penetrance. Therefore, other elements must modify their pathogenicity. Discovery of these modifying factors is not an easy task because in multifactorial diseases conventional genetic approaches may not always be informative.Here, we have taken an evolutionary approach to unmask putative modifying factors for a particular homoplasmic pathologic mutation causing aminoglycoside-induced and non-syndromic hearing loss, the m.1494C>T transition in the mitochondrial DNA. The mutation is located in the decoding site of the mitochondrial ribosomal RNA. We first looked at mammalian species that had fixed the human pathologic mutation. These mutations are called compensated pathogenic deviations because an organism carrying one must also have another that suppresses the deleterious effect of the first. We found that species from the primate family Cercopithecidae (old world monkeys) harbor the m.1494T allele even if their auditory function is normal.In humans the m.1494T allele increases the susceptibility to aminoglycosides. However, in primary fibroblasts from a Cercopithecidae species, aminoglycosides do not impair cell growth, respiratory complex IV activity and quantity or the mitochondrial protein synthesis. Interestingly, these species also carry a fixed mutation in the mitochondrial ribosomal protein S12. We show that the expression of this variant in a human m.1494T cell line reduces its susceptibility to aminoglycosides. Because several mutations in this human protein have been described, they may possibly explain the absence of pathologic phenotype in some pedigree members with the most frequent pathologic mutations in mitochondrial ribosomal RNA.